Application of Photojournalistic Code of Ethics to Legal and Criminal News at Tribun Bone - Raudatul Khairi Nur; Kurniati Abidin (Palakka : Media and Islamic Communication, 2023)
This study discusses the application of the photojournalism code of ethics to legal and criminal news in Tribun Bone. The objectives of this study are (a) to determine the criteria for journalists in publishing photojournalism on legal and criminal news in Tribun Bone, (b) to identify efforts to apply the code of ethics for photojournalism on legal and criminal news in Tribun Bone, and (c) to analyze What obstacles do Tribun Bone journalists face in publishing photojournalism on legal and criminal news in Tribun Bone? The type of research using qualitative descriptive with data sources is journalists in the field of law and crime rubrics and the person in charge of Tribun Bone. Data collection techniques by observation, interviews, and documentation. Data analysis uses Miles and Huberman analysis, which consists of three stages, namely data reduction, data exposure and conclusions. The results showed that, 1) The criteria for photojournalism loading on legal and criminal news in the Bone Tribune are, photojournalism must appear as it is, photos obtained in the field must be sterile from excessive editing . It is done for the sake of validity and honesty of information. If the immoral victim takes it from behind so that the victim's face is not visible, if his face is visible then at the time of loading his face must be blurred. 2) Tribun Bone already understands the existing photojournalism code of ethics and has been implemented in accordance with the code of ethics, but there are still errors from the party The Bone Tribune where some of the news is published still shows the face of the perpetrator of the crime. 3) The first obstacle faced was that it was difficult to obtain photos if not at the time of press release because of limited access for journalists to get images. Second, the lack of communication between journalists at the Bone Tribune, then the third is negligent, forgetting the ethics of existing photos , it is done to compete to provide good news. warmest to the audience.